Existence results for some classes of differential systems with "maxima" - MANGINO, Elisabetta; PASCALI, Eduardo (Studia Universitatis Babeș-Bolyai Mathematica, 2023)
Local existence of solutions of initial value problems associated with a new type of systems of differential equations with ``maxima" are investigated. Mathematics Subject Classification (2010): 34K07. Received 01 April 2021; Accepted 28 July 2021. Published Online: 2023-12-11 Published Print: 2023-12-30